Tác động của rủi ro cảm nhận đến sự hài lòng và ý định quay trở lại điểm đến Lâm Đồng của khách du lịch - Nguyễn Viết , Bằng; Lữ Bá , Văn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study defines and measures the components of risk perception driving tourist’s satisfaction and revisit intention towards Lam Dong province. Data was collected through a survey questionnaire of 473 tourists in Lam Dong. Empirical results investigated the relationship between components of perceived risk, satisfaction, and revisit intention for Lam Dong tourism study. This study also found that female and local tourists perceive risk to be higher than male and foreign tourists. However, the research subject has certain limitations: (i) The survey of this research was conducted in Lam Dong province, (ii) this study used the sampling technique.
Keywords: Revisit intention; Satisfaction; Risk perception; Lam Dong province tourism